2014
DOI: 10.1590/s1981-77462014000200011
|View full text |Cite
|
Sign up to set email alerts
|

Contribuições das comissões de integração ensino-serviço na educação permanente em saúde

Abstract: As comissões de integração ensino-serviço têm um importante papel para a efetivação da Política Nacional de Educação Permanente em Saúde. Neste estudo qualitativo, descritivo e exploratório, objetivouse conhecer os fatores que potencializam ou fragilizam a construção e o desenvolvimento dos planos regionais de educação permanente na concepção dos membros participantes das comissões de integração ensino-serviço do estado do Rio Grande do Sul. A amostra de participantes ocorreu pelo método proposital, intenciona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 4 publications
1
8
0
10
Order By: Relevance
“…In a study conducted in the state of Rio Grande do Sul in 2010, the authors found the lack of evidence of participation and support from managers to be a limiting factor for the operationalization of permanent education actions proposed by the CIES. The lack of knowledge of the managers regarding what is permanent health education and the importance of educational practices to qualify health assistance has generated, often sub-repticiously, obstacles that weaken or prevent its implementation in the region (4,12) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted in the state of Rio Grande do Sul in 2010, the authors found the lack of evidence of participation and support from managers to be a limiting factor for the operationalization of permanent education actions proposed by the CIES. The lack of knowledge of the managers regarding what is permanent health education and the importance of educational practices to qualify health assistance has generated, often sub-repticiously, obstacles that weaken or prevent its implementation in the region (4,12) .…”
Section: Resultsmentioning
confidence: 99%
“…When they participate in the CIES, subjects connected to the teaching experience opportunities that integrate theory and practice, seeing a dialogue between what the theory advocates and what is evidenced in practice (4) . Thus, the teaching-service integration makes it possible to prepare the health professionals to act in a way that is closer to the needs of the population, and this process makes it so the graduation institutions can rethink their role in this setting (5) .…”
Section: The Teaching Institutions Have a Lot To Contribute In Plannimentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the State Coordination Commission (CCE) was created by means of Directive no. 2921 of the Ministry of Health, published on November 28, 2013 14 . This commission, which has its own regulations and is subordinated to the National Coordination Office, aims at drawing the institutions involved in PMMB closer and at helping to solve conflicts and meeting the demands arising during the course of the project.…”
Section: Permanent Education and Teaching-service Integrationmentioning
confidence: 99%
“…O foco do presente trabalho trata de um dos eixos da política -o desenvolvimento dos trabalhadores já inseridos nos serviços -, tendo como pressuposto a relação entre educação e trabalho em saúde, cujo objetivo é induzir as mudanças necessárias no perfil dos profissionais e nas práticas de atenção e gestão dos serviços de saúde do SUS, fomentando o trabalho multiprofissional articulado às necessidades dos atores envolvidos 6,7 .…”
Section: Introductionunclassified